(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Increased demand for conventional energy like coal, natural gas, and oil, forcing researchers to develop renewable or non-conventional energy resources. Renewable energy sources such as fuel cells, wind and solar have received considerable attention because of the ever-increasing demand and electricity expectations. The most prominent and mature technology, including various technologies for harnessing solar energy, is the photovoltaic conversion from sunlight to electricity. Among all the available methods, direct conversion of sunlight into electricity through photovoltaic (PV) phenomenon is the most mature and popular process. Progress of PV technology in market is perspicuous; however, it has still some drawbacks such as notable land requirement in cities, energy conversion efficiencies that already reached the theoretical limits and social acceptance issues due to aesthetic details. To overcome the aforesaid challenges, solar PV tree concept has been recently developed, and the simplicity, compact structure and elegance of this novel technology have been in the focus of researchers. This paper reviews the components, advantages, applications and performance of solar tree. This paper also examines some challenges of solar tree systems.